2008
DOI: 10.2137/145960611797471552
|View full text |Cite
|
Sign up to set email alerts
|

Meat bone meal as fertiliser for barley and oat

Abstract: The traditional production of mineral N and P fertilisers is unsustainable due its reliance on fossil fuels in the case of N, and on limited mineral resource stocks in the case of P. The use of alternative or complementary fertilisers that originate from organic waste materials is gaining interest. Organic farms, especially arable organic farms without livestock, need usable sources of plant nutrients. Meat bone meal (MBM), a potential organic fertiliser for agricultural crops, contains considerable amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
3
39
1
1
Order By: Relevance
“…Salomonsson et al (1994Salomonsson et al ( , 1995 found no significant differences in protein yield for winter and spring wheat at different rates of MBM. However, Chen et al (2011) found a significant increase in the protein yield of spring barley and oat when increasing N level of MBM from 60 to 120 kg ha -1 .…”
Section: Protein Yieldmentioning
confidence: 82%
See 2 more Smart Citations
“…Salomonsson et al (1994Salomonsson et al ( , 1995 found no significant differences in protein yield for winter and spring wheat at different rates of MBM. However, Chen et al (2011) found a significant increase in the protein yield of spring barley and oat when increasing N level of MBM from 60 to 120 kg ha -1 .…”
Section: Protein Yieldmentioning
confidence: 82%
“…Chen et al (2011) found that increasing MBM N from 60 to 120 kg ha -1 significantly increased barley yield. However, in our experiment, increasing N from 118 to 197 kg ha -1 did not increase any of the four crops' grain yields.…”
Section: Grain Yieldmentioning
confidence: 91%
See 1 more Smart Citation
“…Nowadays, cut and polished bones from a variety of animals are sometimes used as a starting material for jewelry and other crafts. Ground cattle bones are used as a fertilizer (Chen et al 2011b). Furthermore, in medicine, bones are used for bone graft substitutes, such allografts from cadavers (Delloye et al 2007) and xenografts (Araújo et al 2009).…”
Section: Bonementioning
confidence: 99%
“…Apart from manure, slurry, sludge and other organic wastes (Hanč et al 2008, Kulhánek et al 2008, meat and bone meals (MBM) can be a viable alternative to phosphate fertilizers (Valenzuela et al 2001, Jeng et al 2006, Svoboda et al 2010, Chen et al 2011, Brod et al 2012, Nogalska et al 2012. Agricultural utilization of MBM has become an important consideration since a complete ban on the feeding of ruminant-derived protein to ruminants, which was introduced to control bovine spongiform encephalopathy (BSE).…”
mentioning
confidence: 99%